Determining Thresholds for Meaningful Change for the Headache Impact Test (HIT‐6) Total and Item‐Specific Scores in Chronic Migraine. Issue 9 (30th August 2020) - Houts, Carrie R.; Wirth, R. J.; McGinley, James S.; Cady, Roger; Lipton, Richard B.
Abstract : Objective: The objective of the analyses described here was to develop thresholds defining clinically meaningful response on the total and item scores of the 6‐item short‐form Headache Impact Test (HIT‐6) in a population of patients with chronic migraine (CM). Background: The HIT‐6 is a short, easily understood, and useful measure of the impact of headache on daily life. Though widely used, limited literature supports a threshold value for clinically meaningful response within individuals over time for the HIT‐6 total score and for the item scores, especially in the CM population. Methods: PROMISE‐2 is a randomized, double‐blind, multicenter study comparing intravenous eptinezumab 100 and 300 mg with placebo for the preventive treatment of CM. Responder definitions for HIT‐6 total and items scores using data from PROMISE‐2 study were calculated via distribution‐based and anchor‐based methods. Distribution‐based methods included half of the baseline standard deviation and baseline standard error of measurement. The change from baseline to week 12 in HIT‐6 scores was assessed using the following anchors: patient global impression of change, reduction in migraine frequency, and change in EuroQol 5 dimensions 5 levels visual analog scale. Values from the literature and PROMISE‐2 analyses were plotted against the cumulative distribution function of change values (baseline to week 12) and used to triangulate to empirically support clinically meaningful change definitions for the HIT‐6 total and item scores in patients with CM. Results: From the literature, 5 articles provided 7 candidate values for a responder threshold for the HIT‐6 total score. From distribution‐ and anchor‐based methods, 5 candidate values were derived from PROMISE‐2 data. Using the median of all candidate values, a HIT‐6 total score responder definition estimate of −6 (ie, ≥6‐point improvement in the total score) appears most appropriate for discriminating between individuals with CM who have experienced meaningful change over time and those who have not. For item‐level analyses using anchor‐based methods, the responder definition for items 1‐3 ("severe pain, " "limits daily activities, " and "lie down") was a 1‐category improvement in response (eg, from Sometimes to Rarely); for items 4‐6 ("too tired, " "felt fed up or irritated, " and "limits concentration"), a 2‐category improvement in response (eg, from Always to Sometimes) was clinically meaningful. Conclusions: Using a multifaceted, statistically‐based approach, the recommended responder definition for the HIT‐6 total score in the CM population is a ≥6‐point decrease, consistent with previous literature. Anchor‐based item‐level responder thresholds were defined as a decrease of 1 or 2 categories, depending on the item. These CM‐specific values will provide researchers and clinicians a means to interpret clinically meaningful change in the HIT‐6 total and item scores and may facilitate the measurement of treatment benefits in specific functional domains of the HIT‐6.